1990
DOI: 10.2176/nmc.30.628
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Pituitary Adenoma and Gangliocytoma Associated with A cromegaly

Abstract: A gangliocytoma in the sellar region is very rare. We report a case of an intrasellar gangliocytoma com plicated by pituitary adenoma presenting with acromegaly. A 52-year-old female was admitted to our hospital with headache, mild acromegaly, and bitemporal hemianopsia, and endocrinological study found a high serum level of growth hormone (GH). A computed tomographic scan revealed a tumor in the sellar region, which was almost totally removed by trans-sphenoidal surgery . Histo logical examination of the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…They are composed of mature ganglion cells with or without a glial component. Gangliocytomas of the pituitary gland are exceptionally rare and usually coexist with a pituitary adenoma, most commonly a GH-secreting adenoma, with the clinical manifestation of acromegaly [4][5][6]12,17,23,27,32,35,39,44,46]; less often, they are associated with ACTH-producing adenomas, and present with Cushing's disease [25,36,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are composed of mature ganglion cells with or without a glial component. Gangliocytomas of the pituitary gland are exceptionally rare and usually coexist with a pituitary adenoma, most commonly a GH-secreting adenoma, with the clinical manifestation of acromegaly [4][5][6]12,17,23,27,32,35,39,44,46]; less often, they are associated with ACTH-producing adenomas, and present with Cushing's disease [25,36,40].…”
Section: Discussionmentioning
confidence: 99%
“…Such neoplasms occur without evidence of adjacent adenoma only occasionally. The majority of ganglion cell tumours appear in association with growth hormone-secreting pituitary adenoma presenting with acromegaly [2,[4][5][6]12,[17][18][19]23,25,32,38,40,42]. They appear less often with adrenocorticotropic hormone-producing adenomas with clinical presentation of Cushing's disease [25,36,40].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, both components of mixed gangliocytoma-pituitary adenoma were demonstrated to produce the hypothalamic releasing hormones (3). All previous reports of mixed gangliocytoma-pituitary adenoma investigating GHRH immunoreactivity have implied GHRH production in the gangliocytic components (Table 1) (1, 5, 6, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19). However, our present case demonstrated that only the adenomatous components may produce GHRH in GH-secreting mixed gangliocytoma-pituitary adenoma.…”
Section: Discussionmentioning
confidence: 90%
“…Approximately 55 cases of sellar gangliocytomas have been reported in the literature only five of them associated with PRL hypersecretion [1][2][3][4]. GH hypersecretion was present in the majority of patients with hormonal excess.…”
Section: Discussionmentioning
confidence: 99%
“…They may occur in association with functioning, usually GH-secreting-, or non-functioning pituitary adenomas. The two cell types, adenomatous and neuronal, may be admixed or may coexist in separate but adjacent tumors [1][2][3][4]. While hyperprolactinemia due to pituitary stalk compression can occur, only rare cases have been described in the literature with the simultaneous presence of a prolactinoma and a sellar gangliocytoma [5,6].…”
Section: Introductionmentioning
confidence: 99%